Congenital Bleeding Disorders and COVID-19 - An Emphasis on the Role of Thrombosis as One of the Main Causes of Morbidity and Mortality in COVID-19 - Dorgalaleh, Akbar; Narouei, Fatemeh; Asadi, Mansur; Khamsi, Hassan M.; Gholami, Mohammad Saeed (Cardiovascular & Haematological Disorders - Drug Targets, 2022)
A turbulent coagulation system is a prominent feature of Coronavirus Disease 2019 (COVID-19), with venous thromboembolism (VTE) a leading cause of death. Our hypothesis is that patients with inherited hypocoagulability, like congenital bleeding disorders (CBD), enjoy a protective effect against COVID-19-induced hypercoagulability and related fatal consequences. Our primary and follow-up observations revealed this effect, at least among patients with moderate to severe congenital bleeding disorders, particularly coagulation factor deficiencies. Theoretically, patients with inherited hypocoagulobility have only a potential protective effect against COVID-19-related hypercoagulability. Yet the lower rate of morbidity and mortality in patients with CBDs suggests that hypercoagulability and thrombotic events are the main cause of death in COVID-19. Therefore, appropriate and timely administration of anticoagulants could significantly decrease the rate of morbidity and mortality in COVID-19.
Keywords: congenital bleeding disorders